2019
DOI: 10.1016/j.invent.2019.100275
|View full text |Cite
|
Sign up to set email alerts
|

Responding to women's needs and preferences in an online program to prevent postpartum depression

Abstract: PurposeGlobal access to adequate resources to address postpartum depression (PPD) are limited and, at times, not reflective of the needs of pregnant women and new mothers. Gathering information about the preferences and needs of women when designing and implementing Internet-based programs is warranted, especially given the diversity of experiences related to childbirth. Thus, the aim of this study was to obtain user feedback on the content, structural, and cultural factors associated with a fully automated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Barrera et al [ 29 ] adapted the program as a self-guided individual internet program that included videos, written materials, and visual summaries. Consistent with our findings, the intervention of Barrera et al [ 45 ] recommended simplification of content, detailed instructions, and graphical representations. Sawyer et al [ 30 , 31 ] also used the MB content as part of a mobile app.…”
Section: Discussionsupporting
confidence: 91%
“…Barrera et al [ 29 ] adapted the program as a self-guided individual internet program that included videos, written materials, and visual summaries. Consistent with our findings, the intervention of Barrera et al [ 45 ] recommended simplification of content, detailed instructions, and graphical representations. Sawyer et al [ 30 , 31 ] also used the MB content as part of a mobile app.…”
Section: Discussionsupporting
confidence: 91%
“…), and participation can be completed at any individual speed. Nowadays one limitation of online depression prevention interventions is poor adherence as this can contribute to reduce their effectiveness (Calear, Christensen, Mackinnon, Kathleen, & Griffiths, 2013;Kelders, Bohlmeijer, & Van Gemert-Pijnen, 2013;Ramphos, Kelman, Stanley, & Barrera, 2019). In our meta-analysis, we found that more interactive online interventions were more effective than more passive ones (Morgan et al, 2012), even if they were delivered with attractive messages and videos (Whittaker et al, 2017).…”
Section: Practical Implicationsmentioning
confidence: 72%
“…This may include solutions for access to technology, resources for digital literacy, or other changes that help historically disenfranchised women feel safe using these tools. The Mothers and Babies Internet Course is a great example of how to do this well; the authors built an internet-based PPD prevention intervention based on evidence-based modalities, and then surveyed a diverse group of mothers about how the intervention could be improved to better reflect the needs of women from diverse backgrounds 35 .…”
Section: Harnessing Promise and Avoiding Pitfallsmentioning
confidence: 99%